The COVID-19 pandemic and fertility decline in Costa Rica: A deep plunge in the first pandemic month, a decelerated decline, and a baby bust due to fleeing migrants - Rosero Bixby, Luis (2024)
Using microdata from the administrative birth registry maintained by the electoral authority of Costa Rica, this paper aims to address the knowledge gap concerning childbearing during the COVID-19 pandemic in the context of rapid fertility decline since before the pandemic, as compared to the scenario in the highly developed countries. Monthly fertility rates for the period between 2018 and 2022 were estimated. The outcome of interest was a year-on-year change in these rates. The major findings of this study are as follows: (i) A short-lived baby bust in the first full month of the pandemic that is similar to falls observed in other countries (the year-on-year decrease of fertility in January 2021 was as high as 24% for some groups); (ii) a pandemic-associated deceleration in the fertility decline, which could be interpreted as a baby boom if the counterfactual were a continuation of the recent pre-pandemic declining trend; (iii) hints of a baby boom later in the pandemic in communities with low socioeconomic status, and especially, in families with several children, which could come from unwanted pregnancies; and (iv) an anomalous drop in births from foreign-born mothers delivered during the first 9 months of the pandemic, which probably stemmed from pandemic-motivated migration out of the country. The fertility plunge in January 2021 seems to be a response to the hardships caused by pandemic mitigation measures in April 2020, as well as by the uncertainties and fears concerning COVID-19, rather than the response to the physiological harm of the disease itself. The native-born Costa Ricans saw some of the lowest total birth rates in the world during the pandemic: 1.14 and 1.13 births per woman in 2021 and 2022, respectively. These rates would have been even lower if the sharp birth decline observed before the pandemic had continued during the two pandemic years under study.